Associations and Dissociations Between Psychoacoustic Abilities and Speech Perception in Adolescents With Severe-to-Profound Hearing Loss. - Kishon-Rabin, Liat; Segal, Osnat; Algom, Daniel (Journal of Speech, Language & Hearing Research, 2009)
Purpose: To clarify the relationship between psychoacoustic capabilities and speech perception in adolescents with severe-to-profound hearing loss (SPHL). Method: Twenty-four adolescents with SPHL and young adults with normal hearing were assessed with psychoacoustic and speech perception tests. The psychoacoustic tests included gap detection (GD), difference limen for frequency, and psychoacoustic-tuning curves. To assess the perception of words that differ in spectral and temporal cues, the speech tests included the Hebrew Early Speech Perception test and the Hebrew Speech Pattern Contrast test (L. Kishon-Rabin et al., 2002). All tests were conducted for the listeners with normal hearing at low and high presentation levels and for the participants with SPHL at 20 dB SL. Results: Only GD thresholds were comparable across the 2 groups at similar presentation levels. Psychoacoustic performance was poorer in the group with SPHL, but only selected tests were correlated with speech perception. Poor GD was associated with pattern perception, 1-syllable word identification, and final voicing subtests. Conclusions: Speech perception performance in adolescents with SPHL could not be predicted solely on the basis of spectral and temporal capabilities of the auditory system. However, when the GD threshold was greater than 40 ms, speech perception skills were predictable by psychoacoustic abilities. Reprinted by permission of the publisher.